Semi-active vibration isolator and fine positioning mount - GRAN; MILTON H; BRONOWICKI; ALLEN J (2000)
A vibration isolation and precision pointing device, and a related method for its operation, for reducing vibrational disturbances on a payload platform, which is subject to vibration transmitted from a base platform and to other possible vibrational disturbances applied directly to the payload itself or to the payload platform. The invention includes a complementary combination of passive isolation and active isolation in parallel between the base and payload platforms, together with a precision positioning system that greatly reduces vibration at very low frequencies. Each isolation device, of which there are three pairs arranged to damp vibration in three axes, includes, in one embodiment, a passive spring to reduce coupling of vibration at higher frequencies and to fulfill a static load bearing function, and an active actuator element, in the form of a voice coil actuator, for applying active compensation over a selected bandwidth of frequencies below that over which passive isolation is most effective. Another disclosed form of each isolation device includes an elastic tube bendable by piezoelectric actuators and having a flexure that transmits the bending force to the payload platform along a single selected axis. In one preferred embodiment of the invention, three pairs of isolation devices are arranged on mutually orthogonal planes that intersect at the center of mass of the payload. As a result, translational vibration in the orthogonal planes is decoupled from rotation of the payload.